Comparative performance analysis of four different combined power and cooling systems integrated with a topping gas turbine plant. (1st November 2020) - Nondy, J.; Gogoi, T.K.
Highlights: Performances of four new combined power and cooling systems are compared. Energy and exergy analyses are done for comparing the systems. Suitable steam pressure in the heat recovery steam generator is identified for each system. The system that gives higher energy output and minimum irreversibility is identified. The gas turbine plant which is common in all contributes more than 95 Abstract: In this paper, the performances of four combined power and cooling systems are compared in which the exhaust heat of a topping gas turbine plant is utilized for further power and cooling generation. Steam turbines (STs) and organic Rankine cycles (ORCs) are used for power generation by integrating those in a completely different arrangement in the first two systems while the third and fourth systems use ST based power cycles. The first and the fourth configuration uses two absorption cooling systems (ACSs) driven respectively by steam and exhaust heat. In the second and third systems, however, only one ACS is used. Energy and exergy based parametric analyses are done, showing the performance variations with HRSG steam pressure from 89 to 94 bar for comparing the CPC systems. The fourth system was found to be the most appropriate from the energetic and exergetic performance viewpoint with the first system to follow. Despite an additional ACS, the total irreversibility of the first and the fourth systems was found almost equivalent to that of the second system. Only in the third system, the total plant irreversibility was relatively less compared to the first and the fourth. It was found that the GT plant alone contributes more than 95% irreversibility in all the four systems.